Efek Penggunaan Metode Pembelajaran Aktif Inovatif Kreatif Efektif Menyenangkan terhadap Prestasi Akademik Pendidikan Agama Katolik Kelas VIII di Sekolah Menengah Pertama Swasta Santo Xaverius 2 Kabanjahe - Erikson Simbolon; Paulinus Tibo; Rudi Hironimus Matondang (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
The study aims to know and analyze the effects of innovative active learning methods that are effective in the most fun and Bahasa, known as the PAIKEM method, judging by learners' academic achievements. The research question is how using innovative, innovative learning methods is particularly pleasant to students' academic achievements in Catholic religious education lesson in class VIII B at a private secondary school Saint Xaverius 2, Kabanjahe. Data is collected from interviews, observation and documentation. The research key informants consist of school teachers, Catholic religious education teachers, and students themselves. An object of research as primary data of the study is the effect of Active, Innovative, Creative, Effective and Fun (PAIKEM) learning methods on the academic achievements of the students. Collected data from the fields will be analyzed using a qualitative approach to reproduce data displays and to conclude research data. To quantify the validity of data research researchers used triangulation both in techniques and sources. Research indicates that the use of PAIKEM learning method brings about a positive impact on the students' academic achievements. The challenge for now is the online study (because of the pandemics). Regardless, it is expected that both online learning and face-to-face learning will be implemented, also in the future.